2015
DOI: 10.1016/j.metabol.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Irisin-encoding gene (FNDC5) variant is associated with changes in blood pressure and lipid profile in type 2 diabetic women but not in men

Abstract: These results indicate that, although not associated with T2DM, the G allele of rs3480 appears to be associated with increased HbA1c, while the T allele of rs1746661 appears to be associated with higher systolic blood pressure and dyslipidemia in women with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In addition, since the discovery of irisin, its levels have been associated with hip fractures [22], sarcopenia [23], insulin resistance [24], chronic obstructive pulmonary disease [25], chronic kidney disease (CKD) [26], and CKD stage [27]. Furthermore, irisin-encoding gene (FNDC5) variant can change blood pressure in men with type 2 diabetes [28], while irisin improves endothelial function in type 2 diabetes [29] and in a mouse model of obesity [30]. In addition, irisin protects against endothelial injury and ameliorates atherosclerosis in Apo-E knockout mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the discovery of irisin, its levels have been associated with hip fractures [22], sarcopenia [23], insulin resistance [24], chronic obstructive pulmonary disease [25], chronic kidney disease (CKD) [26], and CKD stage [27]. Furthermore, irisin-encoding gene (FNDC5) variant can change blood pressure in men with type 2 diabetes [28], while irisin improves endothelial function in type 2 diabetes [29] and in a mouse model of obesity [30]. In addition, irisin protects against endothelial injury and ameliorates atherosclerosis in Apo-E knockout mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…Irisin is a novel myokine that is considered a muscle-derived energy-expenditure signal secreted from the skeletal muscle after cleavage of the myokine fibronectin type III domain containing 5 (FNDC5) in response to exercise and/or peroxisome proliferator-activated receptor-γ coactivation 1a (PGC-1a) [ 44 ]. A diverse array of metabolic actions has been associated with irisin levels [ 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 ]. Irisin levels correlate positively with markers of adiposity, are increased in obesity and irisin resistance might develop in obese individuals [ 67 68 69 70 ].…”
Section: Novel Molecules Important In Energy Homeostasismentioning
confidence: 99%
“…In another cross-sectional study, Brondani et al [17] investigated the association of FNDC5 rs3480 (A/G) and rs1746661 (G/T) polymorphisms with clinical characteristics in 1,006 patients with type 2 diabetes (T2DM) and 434 nondiabetic subjects. They found that the T allele of rs1746661 was associated with increased systolic BP and not diastolic BP, but only in women with diabetes.…”
Section: Irisin and Blood Pressurementioning
confidence: 99%